Distribution and fate of trawling-induced suspension of sediments in a marine protected area. (2nd December 2017) - Linders, Torsten; Nilsson, Per; Wikström, Andreas; Sköld, Mattias; ,
Abstract: Bottom trawls suspend sediments by physical contact and the drag created by the gear when towed over the seafloor. Increased turbidity and redistribution of sediments may be of concern as some organisms are vulnerable to increased levels of sediment particles in the water column. This study investigates the distribution and fate of trawling-induced suspension of sediments in a coastal marine protected area (MPA). Bottom trawling is allowed in a deep trench of the MPA and regulated to weekdays with weekend closures. We use the closed period as controls to experimentally investigate sediment resuspension generated by the trawling fleet. We find that the turbidity is elevated at trawled depths and originates from small particles of silt–mud seafloor origin that remain suspended for days preventing background levels to be reached during closures. Peaks in the plumes behind trawlers reach levels critical to organisms but decays within hours. Currents in the trench are too weak to resuspend sediments; however, wind-induced resuspension events of elevated turbidity likely originating from nearby shallower areas may occur. Short-term closures and small-scale MPAs are concluded to be of limited use as management tools to reduce effects of resuspension by bottom trawling.